Considering Patients’ Mental Capacity When Giving Them Bad News May Help Their Well-Being: A Case of Suicide Attempt after Being Informed of Lung Cancer Diagnosis - Toshiyuki Kobayashi; Satoshi Kato; Mitsuo Takeuchi (Case Reports in Psychiatry)
Mental capacity is a central determinant of patients’ ability to make autonomous decisions about their care and deal with bad news. Physicians should be cognizant of this when giving patients bad news in efforts to help them to cope with the illness and to avoid a deterioration of their mental well-being. To show the importance of this concept, a case of suicide attempt with lung cancer is exemplified. A 76-year-old woman attempted suicide after receiving a diagnosis of lung cancer. Her recent life had been emotionally turbulent and she did not have sufficient mental capacity to accept and cope with this truth. She developed depression before attempting suicide.